2004
DOI: 10.1074/jbc.m405308200
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of Entamoeba histolytica to the Cysteine Proteinase Inhibitor E64 Is Associated with Secretion of Pro-enzymes and Reduced Pathogenicity

Abstract: Cysteine proteinases (CPs) have been considered suitable targets for the development of antiparasitic drugs. To assess the importance of CPs for the growth and pathogenicity of the protozoan parasite Entamoeba histolytica we have cultured amoebae in the presence of various cysteine proteinase inhibitors (CPIs). It was found that broad range CPIs, which are membrane permeable and rapidly enter the cell, are highly toxic at micromolar concentrations, and all attempts to generate E. histolytica mutants resistant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 54 publications
1
20
0
Order By: Relevance
“…1C) as compared with untreated controls. This finding is consistent with a previous report that showed ameba secretes both PCP5 and mature CP5 (27). Thus, to elucidate a specific functional role for EhCP5, colonic cells were exposed to secreted proteinases derived from wild-type (WT), amebapore A vector control (AP ) significantly induced the ubiquitination of NEMO, but CP5 Ϫ/Ϫ did not (Fig.…”
Section: E Histolytica Pcp5 Interacts With Integrin Andsupporting
confidence: 92%
See 3 more Smart Citations
“…1C) as compared with untreated controls. This finding is consistent with a previous report that showed ameba secretes both PCP5 and mature CP5 (27). Thus, to elucidate a specific functional role for EhCP5, colonic cells were exposed to secreted proteinases derived from wild-type (WT), amebapore A vector control (AP ) significantly induced the ubiquitination of NEMO, but CP5 Ϫ/Ϫ did not (Fig.…”
Section: E Histolytica Pcp5 Interacts With Integrin Andsupporting
confidence: 92%
“…With the use of the specific CP5 enzyme inhibitor E64 to abolish CP5 enzyme activity, we were intrigued that it had no effect on PCP5-mediated NFB activation, suggesting that PCP5 may activate NFB. Although previous studies have shown that inhibiting cysteine proteinase activity decreases E. histolytica-induced liver abscess formation, it is important to note that only E64-resistant ameba cultures, rather than wildtype ameba cultured with E64, had a significant effect on liver abscess formation (27). As E64-resistant E. histolytica cultures have significantly decreased CP5 gene expression (27), this finding demonstrates precedence of CP5 as a virulent factor for E. histolytica.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Second, CP-A5 catalytically cleaves pro-MMP-3 into the active enzyme, which in turn activates other MMPs (including MMP-1) and then degrades ECM. It is noteworthy that trophozoites secrete both pro-CP-A5 and mature form 30 , which thus potentially induces and activates human MMPs at the same time. Together, the combined actions of CP-A5 contribute to the ECM destruction by human MMPs and to the acute inflammation observed during intestinal amoebiasis.…”
Section: Discussionmentioning
confidence: 99%